Pale-breasted thrush (Turdus leucomelas) feeds nestlings of the brood parasite shiny cowbird (Molothrus bonariensis) more and faster than its own nestlings - Ferneda, Rafaela Vitti [UNESP]; Batisteli, Augusto Florisvaldo [UNESP]; Pizo, Marco Aurélio [UNESP] (Springer Nature, 2024)
As an evolutionary response to losses caused by brood parasite birds, host species present anti parasitism strategies that may involve the detection and rejection of parasitic eggs and nestlings or the abandonment of the parasitized nest. However, little is known about the capacity of detect and reject the parasitic offspring by hosts in Neotropical birds. Here, we hypothesized that the pale-breasted thrush (Turdus leucomelas) discriminates nestlings of the brood parasite shiny cowbird (Molothrus bonariensis) when providing food. We tested the following predictions (1) thrush nestlings in parasitized nests increase the frequency of begging behavior in response to the loud parasite chicks. As a consequence of host discrimination, (2) thrush nestlings are fed more often than cowbird nestlings, and (3) the time taken by the host parent to select a nestling to be fed is longer for parasite nestlings. We found that the frequency of “lift the head and beg” compared to “lift the head” behavior was higher for cowbirds than for its thrush nestmates in parasitized nests, but thrush nestlings did not change their begging behavior in parasitized and non-parasitized nests. Cowbirds were fed faster and more frequently than thrush nestlings, suggesting that the exaggerated parasite begging calls is an efficient strategy to exploit the parental care provided by pale-breasted thrushes. We conclude that there is no parental discrimination by thrush parents in favor of their own offspring and that the behavior of thrush nestlings is similar when the nestmate is a shiny cowbird or a sibling.
Keywords: Brood parasitism; Parental behavior; Parental discrimination; Turdidae